VD_FINDINFO HC / 2011 / 334 vom 4. Juli 2011 - VD Tribunal cantonal (2011)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN | 125 CC, 163 CC, 176 al. 1 ch. 1 CC, 29 al. 2 Cst., 296 CPC (CH), 308 al. 1 let. b CPC (CH), 310 CPC (CH), 317 al. 1 CPC (CH), 405 al. 1 CPC (CH)